A potential role of cockroaches in the transmission of pathogenic bacteria with antibiotic resistance: A scoping review - Luckyjane Molewa, Mapula; Barnard, Tobias; Naicker, Nisha (The Journal of Infection in Developing Countries, 2022)
Introduction: The role of cockroaches in the cause of disease or human infections is not immediately obvious. The present study aimed to review the currently available research on the potential role of cockroaches in the transmission of pathogenic bacteria and bacteria with antibiotic resistance. Methodology: A scoping review included the studies published for a period between January 2001 and December 2020. A search was performed through five databases, namely, PubMed, Sage, Springer, Sabinet, and Science Direct. A search strategy used was conducted according to the principles of Preferred Reporting Item for Systemic Reviews and Meta-Analyses (PRISMA). From 97 studies identified, 32 studies were included in the scoping review. Results: The findings indicate that cockroaches may be a potential vector for a diverse range of pathogenic bacterial agents. Most bacterial agents isolated are antidrug-resistant and antibiotic-resistant which is considered the greatest threat to public health in the current period. Conclusions: Cockroach infestation should be considered as a serious concern, given the possible role of cockroaches as reservoirs of antibiotic-resistant bacteria. Further research is needed which can provide a comprehensive understanding of the role of cockroaches in transmitting human infections.